Humanitarism and Disaster Governance in Indonesia: Case Study: Merapi Eruption in 2010 - Annisa Gita Srikandini (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2012)
This paper argues that humanitarian action in the aftermath of disaster could be explained with the concept of disaster governance. Humanitarian action has been defined as any action to minimize human suffering wherever it is found without considering any state boundaries. Its goal is to make the affected person to be resilient in the aftermath of disaster. This paper elaborates the principle of disaster governance including the concept of humanitarianism, the development of humanitarian enterprise, and the issue of coordination within the chaotic coordination after disaster. Second, it examines the concept of disaster governance as a model of network. Later, through those both tools, the case of Merapi Eruption in 2010 will be put into context.